Evaluation of the Influence of Sensor Geometry and Physical Parameters on Impedance-Based Structural Health Monitoring - L.V. Palomino; K.M. Tsuruta; J.R.V. Mour Jr; D.A. Radea; V. Steffen Jr.; D.J. Inman (Shock and Vibration)
Structural Health Monitoring (SHM) is the process of damage identification in mechanical structures that encompasses four main phases: damage detection, damage localization, damage extent evaluation and prognosis of residual life. Among various existing SHM techniques, the one based on electromechanical impedance measurements has been considered as one of the most effective, especially in the identification of incipient damage. This method measures the variation of the electromechanical impedance of the structure as caused by the presence of damage by using piezoelectric transducers bonded on the surface of the structure (or embedded into it). The most commonly used smart material in the context of the present contribution is the lead zirconate titanate (PZT). Through these piezoceramic sensor-actuators, the electromechanical impedance, which is directly related to the mechanical impedance of the structure, is obtained as a frequency domain dynamic response. Based on the variation of the impedance signals, the presence of damage can be detected. A particular damage metric can be used to quantify the damage. For the success of the monitoring procedure, the measurement system should be robust enough with respect to environmental influences from different sources, in such a way that correct and reliable decisions can be made based on the measurements. The environmental influences become more critical under certain circumstances, especially in aerospace applications, in which extreme conditions are frequently encountered. In this paper, the influence of electromagnetic radiation, temperature and pressure variations, and ionic environment have been examined in laboratory. In this context, the major concern is to determine if the impedance responses are affected by these influences. In addition, the sensitivity of the method with respect to the shape of the PZT patches is evaluated. Conclusions are drawn regarding the monitoring efficiency, stability and precision.